DESARROLLO DEL MEJORAMIENTO GENETICO EN CUYES EN EL PERU: Formación de nuevas razas - Chauca Francia, Lilia (2023)
The development of the genetic improvement of guinea pigs in Peru can be defined in three stages. The first stage (1965-1970) had as objective to know the characteristics of the species, through the evaluation of native ecotypes and the determination of its productive parameters and behavior. The second stage (1970-2005) had as objective the selection process by productive parameters. In the selection process, productive characteristics with economic implications (body weight and prolificacy) were considered. Once these characteristics were set after 30 generations of selection, they were selected uniformizing their predominant phenotype to search for distinguishability within breeds. The progeny registered in each breed had an internal validation within the INIA stations as well as in the academy. Once this process is completed, it is delivered to producers for validation and multiplication. Analyzing the information generated, the technical files are approved, the official resolutions are issued and the three breeds are released. The Peru breed (2004) is a meat genetic base used in terminal crosses to gain earliness, reaching its commercial weight at 8 weeks with a carcass yield of 73% and feed conversion of 3.01. The Andina breed (2005) was selected by prolificacy, with a fertility of 98.5% and a litter size of 3.4. The Inti breed (2013) was selected by weight and prolificacy, with a litter size of 3.2, weight at 8 weeks of 900 g and a carcass yield of 71.1%. The third stage (2005-2021) begins with interracial crosses, using the Peru breed as the paternal genetic base and the Inti x Andina cross as the maternal genetic base until reaching 5/8 Peru, which was released as the Kuri breed (2021). These crosses seek the best attribute of each breed to achieve a commercial genetic that benefits producers. The Kuri breed is 13.5% larger than the Peru breed in litter size, and 20% and 14% larger in weight than the Andina and Inti breeds, respectively